The Messiah Confrontation : Pharisees versus Sadducees and the Death of Jesus - Knohl, Israel (Book collections on Project MUSE., 2022)
"The Messiah Confrontation argues that Jesus was really convicted and crucified because of a confrontation between two Jewish ideologies"--Provided by publisher.